Time Interval between First and Last Epileptic Seizures and Electroencephalogram Normalization in Benign Childhood Epilepsy with Centrotemporal Spikes: Influencing Factors - Miziara, Carmen Silvia Molleis Galego; Micheletto, Maria Laura Jorge; Serrano, Virginia Aparecida Gelmeti; Nakanishi, Denise Harumi; Serinolli, Mário Ivo; de Manreza, Maria Luiza Giraldes; Reed, Umbertina Conti (Journal of Pediatric Epilepsy, 2020)
The aim of this study was to evaluate the interval between the first and last seizures, the normalization of the electroencephalogram (EEG), and to identify factors of influence. Medical records of children were analyzed with benign childhood epilepsy with centrotemporal spikes. Variables age at first and last seizure, gender, interval between the first and last seizure, the first seizure and EEG normalization, lateralization of the epileptiform discharges, and last epileptic seizure and EEG normalization. The mean time between the first and last seizure was 3.34 years. Early onset of seizures and unilateral discharges were factors that increased the interval between the first and last seizures (p < 0.001). Interval between the last seizure and EEG normalization was 2.40 years, without influence of age (p = 0.986). Interval was shorter in bilateral discharges (p = 0.035). The antiepileptic medicine did not alter the natural history of disease progression. In younger children, the interval between last seizure and normalization of the EEG is reduced compared to older children.
Keywords: benign childhood epilepsy; electroencephalography; Rolandic epilepsy; seizures